2006
DOI: 10.1111/j.1460-9568.2006.05126.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes of neurotrophin mRNA expression in the layers of rat visual cortex

Abstract: Neurotrophins are essential factors for the structural, neurochemical and functional maturation of the brain including developmental and adult plasticity. Northern blots and polymerase chain reaction revealed the expression of neurotrophin 4 (NT4), neurotrophin 3 (NT3), brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) in the cortex. The cellular producers of NT3 and BDNF have been characterized by anatomical methods as being mostly pyramidal, and the tyrosine kinase B (TrkB) receptor is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 56 publications
3
15
0
Order By: Relevance
“…Previous studies have reported uneven distribution of NGF-labeled neurons in the cortical laminae (Pitts and Miller, 2000; Patz and Wahle, 2006). Quantitative analysis by layer was not performed in the current study, however, as NGF labeling intensity diminished with increasing distance from the colchicine injection site.…”
Section: Resultsmentioning
confidence: 92%
“…Previous studies have reported uneven distribution of NGF-labeled neurons in the cortical laminae (Pitts and Miller, 2000; Patz and Wahle, 2006). Quantitative analysis by layer was not performed in the current study, however, as NGF labeling intensity diminished with increasing distance from the colchicine injection site.…”
Section: Resultsmentioning
confidence: 92%
“…It is known that BDNF mRNA expression within primary visual cortex (V1) increases during development (Patz and Wahle, 2006), but while many experimenters examine V1 as a whole, rodent V1 can be broken down into two distinct regions. The monocular portion of V1 (mV1) contains neurons that are driven by only the contralateral eye, but binocular V1 (bV1) contains neurons that are driven by both eyes; thus the effects of visual deprivation in these two regions is not equivalent, and it is not known whether this generates differential regulation of BDNF expression.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a BDNF-dependent modulation of synaptic plasticity at excitatory glutamatergic inputs from the mammillary bodies into the anterior thalamus has been described (Tsanov et al, 2009). However, further BDNF-dependent mechanisms of synaptic modulation have not yet been investigated in the thalamic network, although layer V and VI pyramidal cells, which also project into the thalamus, strongly express BDNF in juvenile and adult rodents (Murer et al, 2001;Patz and Wahle, 2006), and BDNF is highly expressed in the VB of rats during postnatal (P3-P21) development (Mooney and Miller, 2011). Furthermore, TrkB receptor mRNA and TrkB receptor protein are clearly expressed in the ventrobasal thalamus of adult rats (Avwenagha et al, 2006).…”
Section: Introductionmentioning
confidence: 98%